Merawat Jagat, Membangun Peradaban melalui Moderisasi Beragama: Studi Kasus di Desa Galang Suka Kecamatan Galang Kabupaten Deli Serdang - Indriany, Dina; Arya Ardhana, Ahmad; Qorry Prananda Aulia; Sayla Arrahma Hafiidzah; Tahta Nugraha, Rasyid; Rizaka Siregar, Muhammad Sifa; al panzil, Mutiara fadillah (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
Religious moderation is the understanding and practice of religious worship that is balanced, moderate, and not excessive. This paper aims to see whether the Quran and Hadith as the holy book of Muslims have roots and may encourage their followers to commit acts of brutality and fear, especially against individuals of different religions. This study aims to find out how the application of religious moderation, how to care for the universe in Galang Suka Village The results of this study show how moderate life is carried out by the people of Galang Suka Village and what impact it has on the civilization of the surrounding community